‘We make angels’: Rediscovering the Victorian ‘Angel in the House’ in Spike Jonze’s Her (2013) and Denis Villeneuve’s Blade Runner 2049 (2017) (ANU Undergraduate Research Journal, 2019)
Spike Jonze’s 2013 film Her and Denis Villeneuve’s 2017 film Blade Runner 2049 (BR2049) both present spectral female characters who, despite being wholly constructed by futuristic technology, echo the Victorian image of the ‘Angel in the House’. Just as male-engineered changes in technology altered women’s roles and responsibilities in the Victorian period, both Her and BR2049 show the software of their respective female characters to be designed by men. Just as the Victorian ‘Angel’ was perceived as belonging to the domestic sphere, yet denied ownership of property, the technological women of Her and BR2049 are shown to be literally contained within masculine structures, with little personal autonomy. The technologically constructed women are also shown to possess a diminished corporeality, which echoes Victorian conceptions of ideal womanhood as spectral and omnipresent. Lastly, like the ideal Victorian ‘Angel’, both technological women are shown to exert an ameliorative moral influence over their respective male partners. While they present speculative visions of futuristic societies, both Her and BR2049 paradoxically engage with Victorian ideas of the Angel in the House, suggesting an iterated pattern of female experience related to rapid technological change.
Keywords: Her; Blade Runner; Victorian ideals; feminine software; masculine-coded hardware; gender; corporeality